Disruption of hyphal development in Candida albicans ATCC 10231 by bioactive compound from Pseudomonas azotoformans UICC B-91 - Yonita Aprilia Putri, Rina Hidayati Pratiwi, Wibowo Mangunwardoyo (Journal of Applied Pharmaceutical Science, 2024)
Candidiasis and other fungal infections are becoming more frequent. The search for appropriate antibiotics for fungal infections is still ongoing. Pseudomonas azotoformans University of Indonesia Culture Collection (UICC) B-91 has potential as an anticandidal. The purpose of this study was to determine the mechanism of inhibition of the metabolite of P. azotoformans UICC B-91 from the medium against morphologically pathogenic fungi. The results showed metabolite compound P. azotoformans UICC B-91 at a concentration of 100 and 80 mg/ml had strong inhibitory power, and 60 mg/ml had moderate inhibition. Determination of the minimum inhibitory concentration value of the medium solution of P. azotoformans UICC B-91 against Candida albicans American Type Culture Collection (ATCC) 10231 was at a concentration of 7.50 mg/ml. Microscopic observation of C. albicans ATCC 10231 after the addition of P. azotoformans UICC B-91 medium under the light microscope showed inhibition of the transition from yeast to hyphae. Microscopic observation of C. albicans ATCC 10231 after the addition of P. azotoformans UICC B-91 medium under scanning electron microscope showed changes in the yeast cell surface become uneven. The mechanism inhibition of metabolites from P. azotoformans UICC B-91 medium against C. albicans ATCC 10231 is through diffusion that disrupts cell membrane function or inhibits transition from yeast to hyphal form.
Keywords: Anticandidal, C. albicans ATCC 10231, inhibition, mechanism, P. azotoformans UICC B-91